Diseño de material didáctico concreto para la enseñanza de probabilidades en Matemáticas de Bachillerato General Unificado - Vaca Tamayo, Johnny José (2023)
The research objective was to determine the benefits of using concrete didactic material for teaching probabilities in Mathematics in the second year of General Unified High School. It was addressed through a qualitative approach and documentary design, with an exploratory and descriptive character, so the bibliographic review was carried out in journals, thesis, and books, using the technique of the file, in addition, the field information was collected through the survey technique, which was applied to 25 students and the method of the interview formulated to a teacher to collect information. It was identified that the concrete didactic materials capture the attention of the student, furthermore, it was found that to use this material in the classroom, a specific process must be followed in order to help the students to understand the topic and to achieve the skills with performance criteria in the topic of probabilities. Key words: Didactic material, Mathematics, teaching-learning of probabilities.